Uncertainty and management accounting: opportunity, profit opportunity and profit / Akira Nishimura - Akira, Nishimura (Accounting Research Institute (ARI), 2011)
This paper considers the concept of profit in the management cycle, from uncertainty through probability of profit to realization of profit, and reexamines the meanings of profit and risk management in management accounting. As the business management environment becomes more changeable, complicated, and difficult to predict, top leaders in business organizations must more accurately forecast opportunities and risks. Accounting profit tends to be far removed from real-world opportunity. Thus, management accounting that relies on accounting profit can become irrelevant to real business management. This paper reviews the literature on the relationship between uncertainty and profit management with the goal of clarifying the meaning of profit opportunity, which cannot exist without opportunity forecasting and the objective understanding and control of the organizational structure. At the same time, the paper focuses on the importance of continuously paying attention to uncertainty in the business management cycle and the ability of people to perceive risk. The management cycle from opportunity through profit opportunity to realization of profit is presented as a circular model with feed-forward and feedback controls.